The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/art.38975
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SH3 Domain–Binding Protein 2 Function Suppresses Bone Destruction in Tumor Necrosis Factor–Driven and Collagen‐Induced Arthritis in Mice

Abstract: Objective SH3BP2 is a signaling adapter protein which regulates immune and skeletal systems. The purpose of this study was to investigate the role of SH3BP2 in arthritis in human TNF-α transgenic (hTNFtg) and collagen-induced arthritis (CIA) models. Methods First, SH3BP2-deficient (Sh3bp2–/–) and wild-type (Sh3bp2+/+) mice were crossed with hTNFtg mice. Inflammation and bone loss were examined by clinical inspection and histological and micro-CT analyses. Osteoclastogenesis was evaluated with primary bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…(32)(33)(34) In contrast, loss-of-function of SH3BP2 has been shown to protect against inflammatory bone loss in mouse models of RA. (39) In this study, we showed that the SH3BP2-SYK pathway, which is the pathogenic pathway responsible for the rare craniofacial disorder cherubism, is also critically involved in the regulation of alveolar bone resorption in a ligature-induced mouse periodontitis model. Therefore, the current study provides a new example for the concept that studying molecular defects in rare craniofacial diseases can result in a better understanding of the basic pathology of more common diseases and lead to opportunities for novel treatment strategies.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…(32)(33)(34) In contrast, loss-of-function of SH3BP2 has been shown to protect against inflammatory bone loss in mouse models of RA. (39) In this study, we showed that the SH3BP2-SYK pathway, which is the pathogenic pathway responsible for the rare craniofacial disorder cherubism, is also critically involved in the regulation of alveolar bone resorption in a ligature-induced mouse periodontitis model. Therefore, the current study provides a new example for the concept that studying molecular defects in rare craniofacial diseases can result in a better understanding of the basic pathology of more common diseases and lead to opportunities for novel treatment strategies.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, SH3BP2-deficient osteoclast progenitors that are stimulated with RANKL are significantly defective in their bone resorption capacity particularly under inflammatory conditions in cell culture, while maintaining the induction of the master osteoclastogenic transcription factor NFATc1. (38,39) They also fail to develop an organized actin cytoskeleton, which is required for sealing zone formation of bone-resorbing osteoclasts. (38,54) In addition, it has been shown that deletion of Sh3bp2 in osteoclast progenitors by LysM-Cre suppressed in vitro osteoclast bone resorption capability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since cytokines often affect both the inflammatory component and the OC, many experiments need to be interpreted with caution regarding the direct effects of particular pathways on the osteolytic component of disease. The clearest results regarding effects on OC occur when bone loss can be evaluated in the presence of an intact inflammatory response (163165). For example, NIK-deficient mice have reduced bone erosion in inflammatory arthritis models.…”
Section: Introductionmentioning
confidence: 99%